INFLUENCE FITNESS AEROBIC EXERCISE TO INCREASE UPPER BODY STRENGTH AT CADRE POSYANDU ELDERLY UPT PUSKESMAS NGAWI ANVIL DURING COVID-19 PADEMIC - Cahyana, Aris Alfaldieka; Rahayu, Umi Budi; Yantini, Sri (Universitas Muhammadiyah Surakarta, 2021)
Physical fitness is a need that must be met so that we can carry out activities of daily life well. Increasing a person's age will cause a decrease in the function of body cells which can lead to a decrease in physical fitness, one of which is muscle strength. Upper body muscle strength can affect functional activity. To achieve good muscle strength, aerobic exercise is needed. This study aims to determine the effect of aerobic exercise on increasing upper body strength in elderly posyandu cadres.